Management of patients with bleeding disorders and educational needs regarding hemophilia a in 23 italian emergency departments – Results from a survey conducted in Piedmont - Pollio, Berardino; Ricca, Irene; Dainese, Cristina; Valeri, Federica; Valpreda, Alessandra; Linari, Claudia; Borchiellini, Alessandra (Acta Biomedica Atenei Parmensis, 2022)
Background: Haemophilia and von Willebrand disease are the bleeding disorders most frequently encountered in the emergency department (ED), that are often the first point of contact for patients. Evidence suggests that management in the ED is currently suboptimal, mainly because the physicians have few opportunities to deal with this kind of patients. Objectives: We carried out a survey to investigate the management of patients with haemophilia A in Emergency Departments (EDs), and to understand the training needs of the involved physicians. Methods: Overall, in Piedmont Region there are 32 EDs, and considering that our survey was conducted on 21 physicians working in 23 Emergency Departments (EDs), this number is representative of the Region’s reality. The interviews were conducted through face-to-face meetings, including general aspects regarding the clinical characteristics and the management of patients, and self-evaluation of knowledge and interest in receiving information about the disease. Results: In 2019, 131 patients with haemophilia A were admitted (108 adults, 23 paediatric). The best-known and most widely available and used treatments were plasma derivatives, followed by first- and second-generation recombinant FVIII. More recent recombinant and bypassing agents were less known. Half of the interviewees considered their knowledge of bleeding disorders in general and haemophilia in particular to be “basic”, and only one third defined it as “good”; however, 86% expressed great interest in receiving information about the topic. Conclusions: The survey confirms the needs related to the clinical management of rare inherited clotting disorders in EDs. The physicians involved are keen to overcome this lack of knowledge, and proper initiatives should be implemented.